Pelatihan Pembuatan Virgin Coconut Oil (VCO) Bagi Kelompok Perempuan GMIT Jemaat Petra Binilaka Desa Oeltua Kecamatan Taebenu Kabupaten Kupang - Lodowik Landi Pote; Anggelinus Nadut (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
A training activity on making virgin coconut oil (VCO) has been carried out for the GMIT Petra Binilaka women's group, Oeltua village, Taebenu sub-district, Kupang district. This service aims to improve the welfare of the people in Petra Binilaka and can improve the ability and skills of the GMIT women's group to process coconuts into virgin coconut oil (VCO). VCO making training is carried out using the fishing method. This service activity was carried out at the Petra Binilaka Congregation for the women of the GMIT women's group, most of whom were housewives. The target of community service to be achieved is to invite the GMIT Petra Binilaka Women's group who lives in V Binilaka hamlet, Oeltua Village, Taebenu District, Kupang Regency to process coconuts into virgin coconut oil (VCO). The result of the training is that the Petra Binilaka GMIT Women's Group has the ability to process coconuts into virgin coconut oil (VCO) and has an understanding of the benefits of VCO oil from a health and economic perspective and can improve the quality of GMIT women's service programs in the congregation. Keywords: training, practice of making VCO, virgin coconut oil (VCO)